Systematic review of depressive, anxiety and post-traumatic stress symptoms among Asian American breast cancer survivors - William Tsai; Sumaiya Nusrath; Ruidi Zhu (BMJ Open)
Objectives This paper aimed to review the experience of psychopathology symptoms (ie, depressive, anxiety and post-traumatic stress) and their social, cognitive and affective correlates among Asian American breast cancer survivors. Studies on psychosocial interventions for reducing psychopathology symptoms were also included in this review.Design A systematic review was conducted.Methods PubMed, PsycINFO and Web of Science were searched from database inception to November 2018. Empirical, peer-reviewed articles on adult women of Asian heritage residing in the USA with breast cancer diagnoses were included in this review. The methodological quality of the included articles was coded.Results The search yielded 16 empirical articles, which were all deemed to be of high methodological quality. Eleven studies utilised a quantitative design, two studies utilised a qualitative design and three studies utilised a mixed-methods design. Thirteen were cross-sectional and three were longitudinal in design. Only two intervention studies were identified. Studies showed that Asian American breast cancer survivors endorsed moderate to high levels of depressive symptoms, anxiety and post-traumatic stress symptoms; those who are more acculturated demonstrated lower levels of depressive and anxiety symptoms. Asian American breast cancer survivors with social constraints were more likely to have intrusive thoughts and, in turn, have high levels of psychopathology symptoms. Intervention studies were limited, but the use of community-based participatory research approaches and cultural adaptations were noted strengths of the studies.Discussion In addition to discussing clinical implications, we highlight limitations of the literature, including a lack of longitudinal studies and the limited use of standardised diagnostic instruments for assessing psychopathology symptoms among this population. Clarifying the prospective relationships between psychopathology symptoms and their social, cognitive and affective correlates will help inform the development of culturally sensitive psychosocial interventions among Asian American breast cancer survivors.